Design and Construction of Lemang Cook Vertical Type - Zultix Las Risanta; Saipul Bahri Daulay; Achwil Putra Munir (Universitas Sumatera Utara, 2016)
The process of cooking lemang is very simple and has some weakness to be minimalized. The purpose of this research was to design, build, test analyze the economic value of lemang cook. Observed parameters were the effective capacity of the equipment, organoleptic test, and economic analysis.Based on this research it was summarized that the effective capacity, of the equipment was 1,42 kg/hour. The color was 2,9 (like), the formed was 3,1 (like), aroma was 2,9 (like) and taste was 3,3 (like) crispness was 3,5 (crispy). Economic analysis was as follows: basic costs for the first to the fifth year was Rp.4.912,09/kg, Rp. 4.374,57 /kg, Rp .4.195,39 /kg, Rp.4.105,95/kg, and Rp. 4.052,40/kg respectively. Break event point (BEP) for the first to the fifth year was 143.51 kg/year, 77.37 kg/ year, 55.35 kg/ year, 44.36 kg/ year, and 37.78 kg/ year respectively. Internal rate of return (IRR) was 45.87%. Keywords: Glutinous rice, lemang’s, stainless steel lemang’s tube.